Fiscal Expansion in The EU and Scale Effect on Growth Deviations of Developing Economies - Özker, Niyazi (Advances in Social Sciences Research Journal, 2022)
The accelerating effect of financial support and incentives creates different growing trends in countries representing emerging economies. This phenomenon is the subject of other economic growth models in a process in which the expected public supports positively affects emerging economies, including financial monetary policies. Besides the structural effects of the budgetary expansion phenomenon, this study aims to analyse the contribution to economic growth, especially in countries representing emerging economies within the EU’s scope and put forth the scale values for determining possible deviations in response to increasing monetary expansions. These countries have different actual economic growth trends from EU countries, which mean different fiscal policy targets within the scope of the public economy have created other efficiency deviations in expenditure-based policies. It is observed that the fact that public financial support does not appear solely based on public expenditures and that their possible indirect effects on the public budget have a different impact on the target economic growth trends in an expanding fiscal process. Here, the problem for emerging economies is to achieve a controlled fiscal expansion and public spending trends without causing possible macroeconomic deviations from target economic growth. Whether the fiscal-budgetary expansion will include a possible inflationary process in the expansion of the monetary base can also be followed in the empirical process in which the monetary policy targets and the fiscal policies in practice form the basis of possible conflict.